PENERAPAN PEMBELAJARAN LANGSUNG BERBANTUAN MEDIA KOMPUTER UNTUK MENINGKATKAN KEMAMPUAN PENALARAN SISWA - Pasaribu, Sudianto (Jurnal Pendidikan Guru, 2017)
This study aims to: improve the ability of mathematical reasoning class VIII MTs Madinatussalam with the use of computer-aided direct instructional media; and analyze the effectiveness of learning with the use of computer-aided direct instructional media. This research is a classroom action research conducted in class VIII MTs Madinatussalam Percut Sei Tuan subdistrict by the number of students as many as 35 people. The technique of collecting data through observation of mathematical reasoning ability tests, the activities of teachers and students. Based on data analysis conclusions: (1) the use of computer-aided direct instructional media can increase students mathematical reasoning abilities in mathematics teaching material circle first cycle of 40.00%, 85.71% the second cycle, and (2) completeness class rises against mathematics learning of 45.71%. Thus it can be concluded that an increase motivation and mathematical reasoning skills students material circle through the use of computer-aided direct instructional media in class VIII MTs Madinatussalam Percut Sei Tuan subdistrict.